A novel strategy to accurately represent the carrier gas properties of droplets evaporating in a combustion environment. (July 2019) - Sacomano Filho, Fernando Luiz; Krieger Filho, Guenther Carlos; van Oijen, Jeroen Adrianus; Sadiki, Amsini; Janicka, Johannes
Highlights: Vapor pressure calculation strongly interferes with droplet evaporation process. Evaporation models do impact on the speed of flames propagating in droplet mists. Droplet evaporation is sensitive to the presence of combustion products. A computationally efficient method is proposed for evaporation in combustion flows. Abstract: A novel approach to accurately represent the carrier gas thermo-chemical properties of droplets evaporating in combustion environment is proposed and validated in the context of reduced capprhes. Numerical analyses of two of the most employed droplet evaporation models in computational fluid dynamiapplications and their subsequent impact on combustion processes are also performed. The study comprehends a systematic investigation of both models and different procedures used to address the relevant thermo-chemical properties for the evaporation modeling. Initially, investigations are addressed in a single droplet framework. Herein, available experimental data give support to the corresponding discussions. In a second part, both selected models and the simplification using air as carrier gas mixture are investigated in the context of flames propagating in droplets mists. A detailed chemistry model is used to represent the combustion of ethanol in air. A simplification strategy is subsequently investigated in terms of the relevant thermo-chemical properties for the evaporation modeling. The resulting strategy is successfully validated in a numerical context for flames propagating in droplet mists. Results aim to help the choice of methods employed for droplet evaporation modeling in a more general context. The methodology adopted in our analyses allows the assessment of each simplification and converges to an optimal combination of the studied methods.